EFFECTS OF SO2 EMISSION REGULATIONS AND FUEL PRICES ON LEVELLIZED ENERGY COSTS FOR INDUSTRIAL STEAM-GENERATION OPTIONS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
We discuss the impacts of SO2 emission regulations and fuel prices on levellized energy costs of industrial steam generation options. A computer model called INDUSTEAM has been utilized. The steam-supply options comprise conventional grate-firing, bubbling and circulating fluidized beds, fuel-oil, and natural-gas-fired systems. Fuels of different SO2 pollution potential have been evaluated assuming six environmental scenarios and varying fuel prices. A capacity range Of 10-90 MW(th) is covered.
Keywords: REQUIREMENTS; TURKEY